2019
DOI: 10.21037/tcr.2019.06.15
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of radiotherapy in metastatic esophageal cancer: a population-based study

Abstract: Background Population-based estimates of survival benefits of radiotherapy on metastatic esophageal cancer (EC) are lacking. The aim of this study was to analyze survival benefits of radiotherapy in patients with metastatic EC at the time of cancer diagnosis. Methods Patients with metastatic EC were selected from Surveillance, Epidemiology, and End Results databases. The covariates included radiotherapy status, age, sex, insurance, histological type, differentiation, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…This is consistent with a previous Surveillance, Epidemiology, and End Results–based study which found this rate to be 39.9%. 27 The practice patterns were variable, with differences noted across different sociodemographic cohorts and different types of hospitals and regions of the country. It is possible that academic institutions have greater access to advanced endoscopic procedures 28 to palliate symptoms and therefore use radiation less often, although the regional differences could represent different levels of clinician and patient enthusiasm for radiation as a palliative approach in different parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previous Surveillance, Epidemiology, and End Results–based study which found this rate to be 39.9%. 27 The practice patterns were variable, with differences noted across different sociodemographic cohorts and different types of hospitals and regions of the country. It is possible that academic institutions have greater access to advanced endoscopic procedures 28 to palliate symptoms and therefore use radiation less often, although the regional differences could represent different levels of clinician and patient enthusiasm for radiation as a palliative approach in different parts of the country.…”
Section: Discussionmentioning
confidence: 99%